Efficacy of Pfizer-BioNTech in SARS-CoV-2 Delta cluster. (January 2022) - Landsberg, Hannah E.; Turcinovic, Jacquelyn; Sullivan, Madison; Connor, John H.; Hamer, Davidson H.; Platt, Judy T.
Highlights: mRNA SARS-CoV-2 vaccines prevent the spread of the Delta variant. A partially vaccinated individual was protected against the Delta variant after exposure. Epidemiology combined with contact tracing improves outbreak response. ABSTRACT: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) sublineage B.1.617.2 or Delta, a variant that began circulating in India and is becoming dominant in the USA, has been responsible for significant morbidity and mortality. In May 2021, the Delta variant was upgraded to a variant of concern by international authorities. This article reports a cluster of SARS-CoV-2 Delta cases detected in Boston, Massachusetts, in May 2021 involving a recent traveller from India and subsequent transmission to two of three close contacts. All three close contacts experienced the same primary exposure events but differed in vaccination status. The two close contacts that eventually tested positive were unvaccinated. The other close contact had received one dose of the BNT162b (Pfizer-BioNTech) vaccine prior to exposure, and received their second dose 2 days after exposure. This case series illustrates the effectiveness of partial vaccination in blocking transmission of the Delta variant to vaccinated individuals under circumstances where the probability of transmission for unvaccinated individuals is high.